AN INFORMATION SYSTEMS ARCHITECTURE FOR UNIVERSITY HOSPITALS: A CASE STUDY AT HOSPITAL DAS CLI?NICAS OF UFPE - Luz J?nior, Silvano Herculano da (2022)
Enterprise Architecture (EA) has been present in the literature since the 1980s and has been widely applied in several fields, bringing notable benefits in supporting the management and governance of organizations. However, this concept is still little explored when we refer to the application of EA in health systems. The objective of this research in the area of Business Architecture applied to health is to investigate and propose an Information Systems Architecture Model for University Hospitals through a case study carried out at the Hospital das Cli?nicas of the Federal University of Pernambuco (HC- UFPE). The methodological path covered two main stages, with a Systematic Literature Review (SLR) followed by a case study at HC-UFPE. The SRL was developed from a protocol, using the methodology addressed by Kitchenham (2007) and Dyba? & Dings?yr (2008). Nine specific research questions were selected to explore quantitative and qualitative aspects of state of art in applying EA in health. The Cohen's Kappa method was also used to assess the level of disagreement between the two teams of researchers involved in this SLR. The case study considered two primary data collection methodologies, semi-structured interviews, and second participant observation. The data analysis was based on a data triangulation of collected data through open coding, including technical and normative documents from the HC-UFPE. Lastly, the development of an initial Information Systems Architecture modeling the hospital IT sector's current and future business processes. With the SLR, it was possible to identify, from specific research questions, which environments of EA application; what are the positive impacts that EA has brought to the organization; what are the problems and challenges encountered during the application of the EA; and what are the critical success factors for the application of EA. The main publication channels and authors who publish on the topic were also identified. In the case study, the Information Systems Architecture of HC-UFPE was built, using the TOGAF 9.2 framework and the Archi software as a construction tool, aligned with the Archimate language. The data presented here can help IT, and health professionals search for methods to support management hospitals. Regarding the case study, it was possible to present tools that can help in the governance of the HC-UFPE and open doors for new studies to be started for future implementation of EA in the network of university hospitals in Brazil.